A New Direction for Nationalism in Indonesia - Mustopa, Saan; ., Muradi; Sinaga, Obsatar; Sumadinata, Widya Setiabudi (Journal of Ecohumanism, 2024)
In the era of modern Indonesia, marked by the swift flow of globalization and technological advances celebrated enthusiastically, Indonesia faces significant challenges in terms of awareness of nation and state. The onslaught of foreign culture facilitated by media and internet technology can freely present in our society and has the potential to dominate and influence local culture. In addition, other state problems threatened the nation’s sovereignty, especially after 1998, such as the emergence of ideologies contrary to the state ideology, terrorism, radicalism, and social conflicts based on ethnicity, race, and religion. These problems have shifted the meaning of nationalism, especially among the people. Therefore, to deal with these problems, a new understanding and direction related to nationalism is needed so that it can survive during the onslaught of the times. This research aims to conceptualize a new understanding of nationalism using qualitative research methods with a descriptive approach. The results of this study reveal the conceptualization of the understanding of nationalism carried out by Surya Paloh.